Integrating Ethnoscience in Physics Teaching Materials and its Impact on Student’s Science Process Skills and Mastery Concept - Jan Pieter; Putu Victoria M. Risamasu (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to integrate ethnoscience in Enggros and Tobati tribal communities into physics teaching materials and see how it influences students' science process skills and mastery of concepts. The type of research is research and development (R&D) on the 4D model which was modified into 3D without a dissemination stage. The research sample was class XI students at public high schools in Jayapura City. Five validators validated the physics teaching materials developed. To see the effect of using teaching materials, a quasi-experiment was used using a randomized pretest-posttest control group design. The research results showed that the developed teaching materials had a positive impact, and it was found that there were significant differences in science process skills and concept mastery between students who studied with the developed teaching materials and those who studied with conventional teaching materials. The teaching materials developed can mediate student learning transitions and support science process skills and students' mastery of concepts in learning science.